The ethics of HIV / AIDS and the rise of an apocalyptic mariologist Movement for the Restoration of the Ten Commandments : the challenge of HIV / AIDS to Christian theology - Twesigye, Emmanuel K.; Benedicts, Aden S.; Benedicts, Mollie W. (Scriptura : Journal for Contextual Hermeneutics in Southern Africa, 2005)
This article offers an assessment of the significance of The Movement for the Restoration of the Ten Commandments of God (MRTCG) in Uganda. It describes how the MRTCG leaders proposed celibacy and physical withdrawal from the supposed "corrupt, evil and damned world, " and urged their followers to wait for God to destroy the world and to save them through the Blessed Virgin Mary. Tragically, when their apocalyptic prophecies failed to materialize, the MRTCG leaders ritually killed hundreds of their followers in 2000 hoping to save them and through martyrdom, to deliver them directly to God in heaven. It suggests that this movement has to be understood within the context of the rise of HIV / Aids pandemic in Uganda. It describes the socio-economic, cultural, medical and political factors prevailing in Uganda (1981- 2000) and shows how the MRTCG responded to such circumstances. The final section sketches some of the subsequent developments concerning the fight against HIV / Aids in Uganda.
Free